Preliminary Evaluation of a Nuclear Scenario Involving Innovative Gas Cooled Reactors - Barbara Vezzoni; Nicola Cerullo; Giuseppe Forasassi; Emil Fridman; Guglielmo Lomonaco; Vincenzo Romanello; Eugene Shwageraus (Science and Technology of Nuclear Installations)
In order to guarantee a sustainable supply of future energy demand without compromising the environment, some actions for a substantial reduction of CO2 emissions are nowadays deeply analysed. One of them is the improvement of the nuclear energy use. In this framework, innovative gas-cooled reactors (both thermal and fast) seem to be very attractive from the electricity production point of view and for the potential industrial use along the high temperature processes (e.g., H2 production by steam reforming or I-S process). This work focuses on a preliminary (and conservative) evaluation of possible advantages that a symbiotic cycle (EPR-PBMR-GCFR) could entail, with special regard to the reduction of the HLW inventory and the optimization of the exploitation of the fuel resources. The comparison between the symbiotic cycle chosen and the reference one (once-through scenario, i.e., EPR-SNF directly disposed) shows a reduction of the time needed to reach a fixed reference level from ∼170000 years to ∼1550 years (comparable with typical human times and for this reason more acceptable by the public opinion). In addition, this cycle enables to have a more efficient use of resources involved: the total electric energy produced becomes equal to ∼630 TWh/year (instead of only ∼530 TWh/year using only EPR) without consuming additional raw materials.